2016
DOI: 10.18785/goms.3301.09
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Northern Gulf of Mexico Ecosystem

Abstract: The Gulf of Mexico is a large marine ecosystem (LME) bordered by the southern United States, Mexico, and Cuba. This general overview of its northern portion covers physiography, significant oceanographic features, the influence of major rivers and freshwater, biological productivity, and food web characteristics. It then describes the pelagic and benthic components of the major habitats: oceanic (continental slope and abyssal plain), continental shelf and bays, estuaries, and marshes, with descriptions of prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…It is important to note that the overwhelming majority of nGOM mesozooplankton studies focus on the eastern Louisiana shelf (Roman et al, 2012) and the Mississippi Bight (Greer et al, 2016(Greer et al, , 2017Criales et al, 2017;Parra et al, 2019) (but see Gomez et al, 2019). The oceanography of these areas is strongly controlled by the Mississippi-Atchafalaya River (MAR) discharge, where changes in temperature, salinity, and hypoxia are strongly coupled with seasonal changes in river flow (Spies et al, 2016). This relationship between MAR discharge and coastal oceanographic conditions is clearly reflected in the observed drivers of mesozooplankton community structure (Elliott et al, 2012;Roman et al, 2012), with temperature and salinity are the most commonly reported as seasonal drivers (Ortner et al, 1989;Elliott et al, 2012;Greer et al, 2016;Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the overwhelming majority of nGOM mesozooplankton studies focus on the eastern Louisiana shelf (Roman et al, 2012) and the Mississippi Bight (Greer et al, 2016(Greer et al, , 2017Criales et al, 2017;Parra et al, 2019) (but see Gomez et al, 2019). The oceanography of these areas is strongly controlled by the Mississippi-Atchafalaya River (MAR) discharge, where changes in temperature, salinity, and hypoxia are strongly coupled with seasonal changes in river flow (Spies et al, 2016). This relationship between MAR discharge and coastal oceanographic conditions is clearly reflected in the observed drivers of mesozooplankton community structure (Elliott et al, 2012;Roman et al, 2012), with temperature and salinity are the most commonly reported as seasonal drivers (Ortner et al, 1989;Elliott et al, 2012;Greer et al, 2016;Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While estuaries of this region are well studied regarding both physical and biological dynamics (i.e., Galveston Bay; Liu et al, 2017Liu et al, , 2019, much less is known about planktonic systems on the shelf. The Texas area of the LATEX shelf is unique in the nGOM as it retains similar physical qualities of MAR influenced areas (broad shelf, muddy benthos) but with a lower connectedness to MAR discharge (Spies et al, 2016;Du et al, 2019). This lack of freshwater influence may alter hypothesized drivers of seasonal mesozooplankton structure.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions lead to the carbon flux of the midwater column (Bednaršek et al 2012, Burridge et al 2017. Primary production occurs year-round in the northern GoM, but is highest in the spring and summer, coinciding with the Mississippi River's peak discharge (Spies et al 2016). Highly productive areas in the northern GoM yield the highest zooplankton abundances in the GoM (Fisher et al 2016).…”
Section: Spatial Distributionmentioning
confidence: 99%
“…Nutrient loading from the drainage of Midwestern agricultural lands into the Mississippi River is sufficiently high as to cause excessive primary production, oxygen depletion, and a large benthic dead zone of hypoxia reappearing every summer off the coast of Louisiana on an annual basis (Rabalais et al, 2007). Although the Loop Current drives a clockwise circular flow of Gulf waters, cold-core rings spin off frequently enough to induce flows to the northwest ( Figure 2), which introduce additional nutrients into nearshore habitats and generate enhanced primary production fueling pelagic food webs (Spies et al, 2017). While the delivery of nutrients via cold-core rings generally enhances food web production throughout the Gulf, too much nitrogen loading in runoff from land depresses the food web production in a large area off the Louisiana coast.…”
Section: Connecting Land and Seamentioning
confidence: 99%